Chikungunya Virus: An Emergent Arbovirus to the South American Continent and a Continuous Threat to the World - Cunha, Marcela S.; Costa, Pedro A. G.; Correa, Isadora Alonso; de Souza, Marcos R. M.; Calil, Pedro Teles; da Silva, Gustavo P. Duarte; Costa, Sara Mesquita; Fonseca, Vinícius Wakoff P.; da Costa, Luciana J. (Frontiers in Microbiology, 2020)
Chikungunya virus (CHIKV) is an arthropod-borne virus (arbovirus) of epidemic concern, transmitted by Aedes ssp. mosquitoes, and is the etiologic agent of a febrile and incapacitating arthritogenic illness responsible for millions of human cases worldwide. After major outbreaks starting in 2004, CHIKV spread to subtropical areas and western hemisphere coming from sub-Saharan Africa, South East Asia, and the Indian subcontinent. Even though CHIKV disease is self-limiting and non-lethal, more than 30% of the infected individuals will develop chronic disease with persistent severe joint pain, tenosynovitis, and incapacitating polyarthralgia that can last for months to years, negatively impacting on individual’s quality of life and socio-economic productivity. The lack of specific drugs or licensed vaccines to treat or prevent CHIKV disease associated with the global presence of the mosquito vector in tropical and temperate areas, representing a possibility for CHIKV to continually spread to different territories, making this virus an agent of public health burden. In South America, where Dengue virus is endemic and Zika virus was recently introduced, the impact of the expansion of CHIKV infections, and co-infection with other arboviruses, still needs to be estimated. In Brazil, the recent spread of the East/Central/South Africa (ECSA) and Asian genotypes of CHIKV was accompanied by a high morbidity rate and acute cases of abnormal disease presentation and severe neuropathies, which is an atypical outcome for this infection. In this review, we will discuss what is currently known about CHIKV epidemics, clinical manifestations of the human disease, the basic concepts, and recent findings in the mechanisms underlying virus-host interaction and CHIKV-induced chronic disease for both in vitro and in vivo models of infection. We aim to stimulate scientific debate on how the characterization of replication, host-cell interactions, and the pathogenic potential of the new epidemic viral strains can contribute as potential developments in the virology field and shed light on strategies for disease control.